2020
DOI: 10.1089/hum.2019.312
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Oncogene Manipulation Using Clustered Regularly Interspersed Short Palindromic Repeats/Cas9 Delivered by pH-Sensitive Cationic Liposomes

Abstract: Clustered regularly interspaced short palindromic repeat (CRISPR)/CRISPR-associated protein 9 (Cas9) technology enables targeted gene editing, but cancer gene therapy with this approach requires improvements to enable safe and efficient delivery of CRISPR/Cas9 to tumors. We developed and evaluated a self-assembled liposome to selectively deliver CRISPR/Cas9 to cancer tissues. Our CRISPR/Cas9 system effectively inhibited proliferation of human papillomavirus (HPV) 16-positive cervical cancer cells and induced a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 30 publications
0
41
0
Order By: Relevance
“…In vivo experiments in mice showed that these nanoliposomes significantly inhibited tumor growth without toxicity. Therefore, this system can be considered a valuable delivery carrier of nonviral gene editing elements, offering a promising route to precision medicine-based cancer therapeutics [69].…”
Section: Human Papillomavirus (Hpv)mentioning
confidence: 99%
“…In vivo experiments in mice showed that these nanoliposomes significantly inhibited tumor growth without toxicity. Therefore, this system can be considered a valuable delivery carrier of nonviral gene editing elements, offering a promising route to precision medicine-based cancer therapeutics [69].…”
Section: Human Papillomavirus (Hpv)mentioning
confidence: 99%
“…The introduction of a tunable tissue-specific method for delivering LNPs opens potential therapeutic applications for lipid-mediated delivery of Cas9. In a separate study, an alternative strategy for tissue-targeted delivery of Cas9 was demonstrated using pH-sensitive liposomes [ 200 ]. The authors demonstrated that pH-sensitive liposomes disassembled in the presence of the tumor microenvironment, releasing the Cas9 protein and allowing for gene editing.…”
Section: Delivery Strategies For Therapeutic Applicationsmentioning
confidence: 99%
“…Delivery systems can be broadly categorized into lipids, polymers, peptide/protein nanovesicles, and extracellular vesicles ( Figure 1, Table 1). [30] hydrophilic head groups. These amphipathic lipids self-assemble in a physiological aqueous environment, forming vesicles with a bilayer structure.…”
Section: Nonviral Delivery Systems For Genome Editingmentioning
confidence: 99%
“…Another study utilized DOTAP-based cationic liposome for delivery of pCas9 and viral protein-specific sgRNA to treat cervical cancer [30]. In this study, liposomes composed of DOTAP, DOPE, cholesterol, and DSPE-PEG-2000 were complexed with human papillomavirus 16 E6/E7 (HPV 16 E6/E7)-specific sgRNA and pCas9.…”
Section: Nonviral Delivery Systems For Genome Editingmentioning
confidence: 99%